Trzy szubienice. Paszkwile na biskupów: Stanisława Józefa Hozjusza, Jana Aleksandra Lipskiego oraz Krzysztofa Antoniego Szembeka z okresu przedostatniego bezkrólewia i walki o koronę polską (1733–1736): - - Trościński, Grzegorz (Prace Polonistyczne, 2019)
The article is an analysis of pasquils about Bishops Stanisław Józef Hozjusz, Jan Aleksander Lipski and Krzysztof Antoni Szembek. There are the pieces of occasionally political poetry from the period of the interregnum after the death of August II Sas and the fight for the crown by two rivals: his son’s August III and Stanisław Leszczyński (in the years 1733–1736). The Bishops, who come under attack, were adherents of Fryderyk August, but the occasional poetry was written by adherents of Leszczyński, August’s political antagonists. The article presents various political faults, symbols of betrayal, and heraldic conceits which were used to bring discredit on clergy. The author shows the adopted strategies which were used in the polemical poems.